Development and surges of organized crime: an application of enterprise theory - Albanese, Jay S. (Organized crime in the 21st century, 2023)
Major events and surges in organized crime activity in the United States and elsewhere over the last 100 years are used to illustrate how the enterprise perspective can be used to explain how and why these changes occur. The analysis is followed by an examination of recent case prosecutions, offering insights into the current manifestations of organized crime offenses, groups, and their international links, together with their connections to the past. Using cigarette smuggling and trafficking in cultural property as examples, both the shifts over time in organized crime activity and the responses to them are shown to be the result of interactions between available supply, demand, regulation, and competition in specific illicit markets. Implications are presented for both the short- and long-term prospects for organized crime opportunities and its prevention through an empirical risk assessment approach.